Double wedge model for computing seismic sliding displacements of cantilever retaining walls. Issue 116 (January 2019) - Jadhav, Prajakta R.; Prashant, Amit
Abstract: A double wedge model has been proposed to compute seismic sliding displacements of cantilever retaining walls. Experimental observations indicate formation of rupture planes in the form of an inverted triangular wedge in the backfill of retaining walls. Computation of critical yield acceleration at each time instant considering the v-shaped weakest rupture planes which evolve during the ground motion is the preliminary aim of the double wedge model. The model computes translational displacements considering the relative movement of soil wedge along these rupture planes. It considers velocity compatibility along with the acceleration compatibility between the wall and soil wedge. It also computes approximate depth of subsidence of the backfill soil during ground motion. A simplified double wedge model has been also considered wherein the yield acceleration at all time instants is computed with respect to a fixed wedge. The double wedge model and its simplified version have been compared with different cases studies, which show the seismic sliding displacements matching well with the real measurements. Highlights: A model to compute seismic sliding displacements of cantilever walls is proposed. It considers formation and relative movement of v-shaped wedges in the backfill. It ensures velocity compatibility of this wedge with respect to wall and backfill. It computes approximate depth of subsidence of backfill during ground motion. A simplified model is also proposed which considers movement of fixed wedge.